PENGARUH MEDIA GOOGLE EARTH TERHADAP HASIL BELAJAR BERDASARKAN KEAKTIFAN SISWA KELAS IV TEMA INDAHNYA NEGERIKU DI SEKOLAH DASAR - Putra, Aldoko Listiaji; Kasdi, Aminuddin; Subroto, Waspodo Tjipto (Universitas Negeri Surabaya, 2019)
ABSTRACTThe main purpose of this research is: 1) to describe the effect of the google earth media to student learning outcomes, 2) to describe the effect of student activeness to student learning outcomes, 3) to describe the interaction effects between google earth media and student activeness to student learning outcomes. This research was conducted at SDN Lidah Kulon 1 Surabaya with research subjects are students of Fourth Grade Student B as the control class and Fourth Grade Student C as an experimental class of the school year 2015/2016. Type of research is experimental. The data was obtained as follows: (1) there is the effect of the google earth media to student learning outcomes. With the same test two way of anova significance value the effect cognitive ability level of 0.002<0.05, (2) there is a activeness the effect to student learning outcomes. This conclusion is drawn from the results of empirical tests using two way of anova. With the test results show the value of the activity's significant the effect to student learning outcomes of 0,023<0,05, (3) there is no interaction effect of media and activeness to student learning outcomes. This conclusion is drawn based on two way of anova showed significant value interaction effect of media and activeness to student learning outcomes of 0.547> 0.05. Based on the research, it can be concluded that: (1) google earth media have a significant effect to the learning outcomes of students, (2) activeness have a significant effect to the learning outcomes of students, (3) there is no significant effect from the interaction between the media and the activeness to student learning outcomes. Keywords: Google Earth, Activeness, Learning Outcomes. ABSTRAK Tujuan utama penelitian ini adalah: 1) untuk mendeskripsikan pengaruh media google earth terhadap hasil belajar siswa, 2) untuk mendeskripsikan pengaruh keaktifan siswa terhadap hasil belajar siswa, 3) untuk mendeskripsikan pengaruh interaksi antara media google earth dan keaktifan siswa terhadap hasil belajar siswa. Penelitian ini dilakukan di SDN Lidah Kulon 1 Surabaya dengan subjek penelitian adalah siswa kelas IV B sebagai kelas kontrol dan IV C sebagai kelas eksperimen tahun pelajaran 2015/2016. Jenis penelitian yang dilakukan adalah penelitian eksperimen. Data hasil penelitian yang diperoleh sebagai berikut: 1) terdapat pengaruh media google earth terhadap hasil belajar siswa. Dengan uji yang sama yakni uji anava dua jalur diperoleh nilai signifikansi pengaruh tingkat kemampuan kognitif sebesar 0,002<0,05, 2) terdapat pengaruh keaktifan terhadap hasil belajar siswa. Kesimpulan ini diambil mengacu pada hasil uji empiris menggunakan anava dua jalur. Dengan hasil uji menunjukan nilai signifikansi pengaruh keaktifan terhadap hasil belajar siswa sebesar 0,023<0,05, 3) tidak terdapat pengaruh interaksi keaktifan dan media terhadap hasil belajar siswa. Kesimpulan ini diambil berdasarkan hasil uji anava dua jalur yang menunjukan nilai signifikansi pengaruh interaksi media dan keaktifan terhadap hasil belajar siswa sebesar 0,547>0,05. Berdasarkan hasil penelitian, dapat disimpulkan bahwa: 1) media google earth terhadap hasil belajar siswa menunjukan terdapat pengaruh yang signifikan, 2) keaktifan terhadap hasil belajar siswa menunjukan terdapat pengaruh signifikan, 3) interaksi antara media dan keaktifan tidak memiliki pengaruh signifikan terhadap hasil belajar siswa. Kata Kunci : Google Earth, Keaktifan, Hasil Belajar.